Pengaruh Debt To Equity Ratio Dan Price Earning Ratio Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Moderating Pada Perusahaan Manufaktur(Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024) - Syukri Ramadhan; Berta Agus Petra; Nila Pratiwi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of the Debt to Equity Ratio (DER) and Price Earnings Ratio (PER) on firm value, with financial performance as a moderating variable. The object of this research is manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The population of this study consists of 41 companies, with a sample of 21 companies selected using a purposive sampling technique, resulting in 105 observations. The data used are secondary data obtained from the companies’ annual financial statements published on the official IDX website. The data analysis method employed is panel data regression using EViews 10 software, while the moderation analysis is conducted using Moderated Regression Analysis (MRA).The results indicate that the Debt to Equity Ratio has a significant effect on firm value, whereas the Price Earnings Ratio does not have a significant effect on firm value. Furthermore, financial performance, proxied by Return on Assets (ROA), is able to moderate the effect of the Debt to Equity Ratio on firm value, indicating that the impact of leverage on firm value is highly dependent on the company’s financial performance. In addition, financial performance is also able to moderate the effect of the Price Earnings Ratio on firm value, but with a weakening moderating effect. This finding suggests that in companies with strong financial performance, investors do not rely solely on market ratios such as PER, but place greater emphasis on the company’s actual financial performance when assessing firm value.